Stress-host-parasite interactions: a vicious triangle? (VERSION IN SPANISH): Versión en español (FAVE Sección Ciencias Veterinarias, 2016)
The potential for synergy between host physiological condition and infection has recently been recognised. Here we review the evidence to support the idea that stress may play a key role in the interplay between host and parasite, integrating a three-way circular synergistic interaction between stressors, infections and host response: chronic stress can elicit responses that impoverish the host’s physiological condition (including its immune function), which predisposes to infection, which results in more stress, and so on. We argue that this introduces additional explanatory power to previous ideas posited by the authors, by including stress as a third interacting factor that intervenes in the synergy between condition and infection.  This in turn, may have important implications. In nature, evolutionary forces appear to select against stress-related disease or exacerbated parasite virulence. Nonetheless, under certain circumstances, parasites and (other) stressors interact generating a vicious spiral that may affect host fitness and survival. At high host densities, this becomes a mechanism of population regulation. Also, anthropogenic stressors may cause this mechanism to misfire, with significant implications for biological conservation and public health.
Keywords: vicious circles